ANOD 3G development of a cost-effective GPS-tracked data logging drifter with GSM and parameter gathering capabilities - Belbes, Jet Lawrence M.
Knowledge on ocean circulation patterns and other related oceanic activities precedes the determination of effects on weather patterns, global transfer of organisms, nutrients and potential pollutants, and marine biological diversity, which are essential constituents of aquatic studies. Drifter technology provides information on ocean current behavior and oceanic parameters such as temperature, salinity, pH, etc. Though many aquatic monitoring studies have already been done in the Philippines, existing monitoring practices either use manual methods or involve expensive technologies. ANOD 3G is a Sea Surface Drifter System that composes of three major blocks: sensing, localization, and telemetry. The ANOD 3G System's drifter aims to be a cost-effective Global-Positioning-System (GPS) tracked, data-logging, floating drifter with an efficient telemetry scheme to assist in Philippine marine studies and promote an extensive and autonomous marine monitoring system. The sensing block makes use of sensors for sea-surface temperature, salinity data, and sea-state measurements with dynamic sampling and datalogging capabilities. The localization block, which a utilizes a GPS module, provides the geographic coordinates of the system at a given time. The GPS coordinates, temperature, salinity, wave height, and wave period values, signal coverage and battery voltage are stored in a Memory card and can be sent via the telemetry block through Global System for Mobile (GSM) Short Message Service (SMS) messaging. Data transmission through the GSM is set to periodically transmit data (auto-report) to the base station. The system will be equipped with a Graphical User Interface (GUI) and a Database on the base station to aid in the presentation and storage of data. To evaluate the performance of the system, different tests is conducted for the individual system components as well as for the system as a whole based on hardware design durability, data transmission reliability, measurement accuracy and power consumption properties.